Detecting Hidden Violence: The Spatial Distribution of Excess Mortality in Rwanda - Marijke Verpoorten (Katholieke Universiteit Leuven, LICOS Centre for Institutions and Economic Performance, 2010)
Rwanda experienced several firms of internal violence, including civil war,genocide, reprisal killings and (counter-)insurgency. While these events all occurred in 1990-1998, their geographic location within Rwanda differred, with the genocide especially severe in the South of the country, the civil war and reprisal killings mostly taking place in the North and East, and the (counter-)insurgency concentrated in the Northwest. In order to assess the relative impact of the different firms of violence, this article derives a detailed spatial pattern of excess mortality from the population census. In line with previous evidence on the death toll of firmed conflict in Rwanda, we find significant high-high excess mortality clusters in the southern province of Butare, in and around Kigali City, and in the eastern province Kibungo. Furthfirmore, we present the first quantitative evidence to date of high excess mortality in the northwestern porvince Gisenyi, indicating that the 1995-1998 (counter-)insurgency inflicted a much higher death toll on the population than presently acknowledged by the Rwandan government, the UN and large western donors.
Keywords: J11; J15; Y80; 330; armed conflict; genocide; excess mortality; Rwanda; Politische Unruhen; Bürgerkrieg; Sterblichkeit; Räumliche Verteilung; Ruanda